2022
DOI: 10.4110/in.2022.22.e17
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Diversity during Early Infancy Increases Microbial Diversity and Prevents Egg Allergy in High-Risk Infants

Abstract: We aimed to investigate associations of dietary diversity (DD) with gut microbial diversity and the development of hen's egg allergy (HEA) in infants. We enrolled 68 infants in a high-risk group and 32 infants in a control group based on a family history of allergic diseases. All infants were followed from birth until 12 months of age. We collected infant feeding data, and DD was defined using 3 measures: the World Health Organization definition of minimum DD, food group diversity, and food allergen diversity.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 27 publications
(44 reference statements)
0
15
0
Order By: Relevance
“…A Korean study reported that higher diet diversity scores at 3, 4 and 5 months of age were associated with increased microbial diversity at 6 months. Gene expression of pro‐inflammatory and Th2‐cytokines and chemokines, IL‐4, IL‐5, IL‐6 and IL‐8, were higher among infants with lower diet diversity scores than those with higher diet diversity scores 89 . High‐risk infants with a higher food allergen diversity score at 5 months of age showed a reduced gene expression of IL‐13 89 .…”
Section: Nutrients and The Microbiomementioning
confidence: 96%
See 2 more Smart Citations
“…A Korean study reported that higher diet diversity scores at 3, 4 and 5 months of age were associated with increased microbial diversity at 6 months. Gene expression of pro‐inflammatory and Th2‐cytokines and chemokines, IL‐4, IL‐5, IL‐6 and IL‐8, were higher among infants with lower diet diversity scores than those with higher diet diversity scores 89 . High‐risk infants with a higher food allergen diversity score at 5 months of age showed a reduced gene expression of IL‐13 89 .…”
Section: Nutrients and The Microbiomementioning
confidence: 96%
“…89 High-risk infants with a higher food allergen diversity score at 5 months of age showed a reduced gene expression of IL-13. 89 A recent study in pregnant women showed that increased healthy diet diversity in pregnancy was associated with reduced offspring allergy outcomes defined as 'all allergies excluding wheeze' by 4 years, but microbiome data were not available. 90 Data regarding diet diversity in the adult population and food allergy are lacking.…”
Section: Guidance Population/recommendations Age To Introducementioning
confidence: 98%
See 1 more Smart Citation
“…reported that reduction in food diversity at 12 months of age was significantly associated with an increased risk of parent-reported food allergy by 2 years of age. A research group from Korea [ 89 ] reported higher DD based on food group consumption, number of food allergens consumed, and the WHO definition of diversity at 3 and 4 months were associated with a lower prevalence of hen’s egg allergy in the high-risk group. No associations were seen in the control group.…”
Section: Infant Ddmentioning
confidence: 99%
“…Recently, the EAT study showed that the introduction of 6 major allergenic foods leads to a significant increase in microbial diversity, measured by the Shannon index and increase of Prevotellaceae and Proteobacteria, compared with exclusively breastfed infants [ 111 ]. A Korean research group reported data on DD in infancy, gut microbial composition and development of hen’s egg allergy [ 89 ]. DD was defined according to the WHO definition of minimum DD, food group diversity, and food allergen diversity.…”
Section: The Bigger Picture Of Preventionmentioning
confidence: 99%